Ælfric's Interjections: Learning to Express Emotion in Late Anglo-Saxon England. - Hobson, Jacob (Review of English Studies, 2018)
Ælfric's Grammar offers the only theoretical treatment of emotions in Old English. According to Ælfric, it is the special property of interjections that they express emotion. This article explores what it meant for monastic students to learn to express their emotions using Latin interjections, considering their use in the classroom, the liturgy, scriptural study, and spontaneous speech. The use of interjections, as Ælfric and other medieval scholars of language understood them, raises larger theoretical questions: can the expression of emotion be translated across languages? Is it willed or unwilled? Is it a natural sign like facial expressions or a conventional sign like other words? How, in other words, can a monastic subject map his interior experience onto the Latin language and manage its expression in the monastery? To answer these questions, this article studies not only Ælfric's late tenth-century Grammar but also the Continental tradition of grammatica that lay behind it, explaining a crucial stage in the formation of the monastic subject.